Dielectric and ferroelectric properties of Ba(Ti 0.82Sn0.18)O3ceramics prepared by two-steps sintering - Chatchai Kruea-In (2018)
The method of two-steps sintering was applied to Ba(Ti0.8 2 Sn 0.18 )O 3 ceramics to improve their electrical properties. The ceramics were sintered at T 1 (1350°C) with a short time, followed by firing at T 2 (1100°C) for 4-16 h. Effects of dwell time at T 2 on the properties of the ceramics were investigated. The examination of dielectric spectra indicates that the ceramics exhibited a relaxor behavior. An improvement in density and dielectric constant at the transition temperature of the ceramics were observed for a longer dwell time. The dielectric behavior was confirmed by the ferroelectric behavior of the samples. © 2013 Copyright Taylor and Francis Group, LLC.